Hutsuls' perceptions of forests and uses of forest resource in Ukrainian and Romanian Bukovina. (1st September 2022) - Mattalia, G.; Stryamets, N.; Balázsi, Á; Molnár, G.; Gliga, A.; Pieroni, A.; Sõukand, R.; Reyes-García, V.
Socio-economic and political contexts play a major role in a community's perception of the environment, determining natural resource use. We examined perceptions of forest and forest resource use among two Hutsul communities in Bukovina sharing a similar cultural background but living in a region divided by the national border created between Romania and Ukraine in the 1940s. Twenty-nine open-ended and 61 semi-structured interviews were conducted with Hutsuls from Romania and Ukraine. Hutsuls across the border mostly share perceptions of forest benefits, while they differ in perceptions of environmental changes and the drivers of these changes. Hutsuls of Ukraine showed a greater connectedness and a stronger tie to the forest as an essential element of their livelihoods. Moreover, Hutsuls in Ukraine rely more on forest medicinal plants than do Hutsuls in Romania. Hutsuls' perspectives on the negative impact of current forest management policies should be a cornerstone for redesigning sustainable forest management plans.